Trigg family papers - King, George Harrison Sanford
Correspondence, cards, miscellaneous notes, and clippings of the Trigg family. Also, typed copy of "The Family of Captain John Carter of Spotsylvania County, Va." by George Harrison Sanford King.
Collection material in English.
Keywords: Carter, John, -- approximately 1720-; Carter family; Trigg family; Spotsylvania County (Va.) -- Genealogy; Virginia -- Genealogy